Comprehensive management of gestational diabetes mellitus: practical efficacy of exercise therapy and sustained intervention strategies - Xu, Hao; Liu, Renyi (Frontiers in Endocrinology, 2024)
Background Gestational Diabetes Mellitus (GDM) affects 14.0% of pregnancies globally, with a 35% post-pregnancy relapse and a 60% risk of Type 2 Diabetes (T2D) within 5-10 years. Challenges in long-term management, especially postpartum, include adherence and follow-up difficulties.This study, based on a systematic review and meta-analysis, examined the practical effects of exercise therapy in the prevention, treatment, and prevention of progression from Gestational Diabetes Mellitus (GDM) to Type 2 Diabetes (T2D). Relevant research and clinical practices were retrieved from six major databases (PubMed, Scopus, Web of Science, Cochrane Library, MEDLINE, Science Direct). After analyzing the intervention effects of exercise therapy at different stages, factors favorably influencing the effectiveness of exercise intervention were identified during the more effective stages. Finally, a long-term and efficient exercise implementation plan for the comprehensive management of GDM was proposed.In GDM prevention, exercise reduced the post-intervention risk by 37% compared to the control group (Relative Risk (RR)=0.63; 95% Confidence Interval (CI): 0.54 to 0.72; p=0.01).Studies on GDM treatment showed improved glucose control in the exercise group post-intervention (Mean Difference (MD)=-0.10; 95% CI: -0.16 to -0.04; p=0.04 / MD=-0.27; 95% CI: -0.36 to -0.19; p<0.0001). However, exercise therapy didn't significantly affect the incidence of T2D post-GDM (RR=0.88; 95% CI: 0.69 to 1.11; p=0.39) due to challenges in quantified exercise prescriptions and the complexity of postpartum programs.To enhance exercise therapy effectiveness in GDM management, the study recommends adopting an integrated model emphasizing personalized pregnancy plans, postpartum strategies, and long-term support. Leveraging frequent healthcare contact during pregnancy can establish and sustain exercise habits, fostering a lifelong pattern. While the study acknowledges limitations, this approach holds potential for improving glycemic metabolism and developing healthy exercise habits in subsequent generations. Future research should include longer follow-ups to validate the practical efficacy of this approach in preventing T2D after GDM.